Monitoring and testing of a new stone masonry arch bridge in Vila Fria, Portugal - António Arêde (2007)
This paper reports on the monitoring and load testing of a new stone masonryarch bridge recently built over the river Vizela in Vila Fria, Felgueiras, located about 60 kmfrom Porto, Portugal. Besides highlighting the scientific purposes subjacent to this bridgeconstruction initiative, the paper addresses basic aspects on the installed instrumentation andprovides a general overview of sensor types, location and measured signals, as well as dataacquisition and transmission systems. Some of the most relevant result measurements obtainedfrom the load test and their comparison with available numerical analyses are also presented.